Towards a Conception of the Continuous Structure of Cognition. A Peircist Approach (2024)
This paper presents a model of the continuous structure of Cognition based on several theses proposed by Charles S. Peirce in his youth and in his mature period. In this model, cognitions are discontinuous parts on a continuum and a cognitive process becomes “individually-synthetic,” as a hypostatic abstraction from discontinuous transformations of informational fluxes in the continuous course of experience. That is, they are salient regions or neighborhoods on a continuum rather than points, and the relations of succession and precession among them are inferential, fluid, time sensitive, and goal-directed. First, this paper will outline the theses found in the young Peirce’s work, which inspire a conception of continuous Cognition. Two questions will be raised regarding such a conception: (1) at what point does a particular act of cognition conclude? and (2) how should we characterize individual cognitions? To address these questions, the paper will later introduce the concept of continuity that Peirce developed in his mature years. The synthetic character of the continuum leads to the formulation of the concepts of neighborhood and synthetic individuality. These notions support the conception of a continuous model of Cognition in which the relations of succession and precession between individual finite cognitions are explained. The paper ends with a brief reflection regarding the possibility of developing this model of continuous Cognition as a theory of extended cognition.